The impact of selected environmental, behavioral and psychosocial factors on schoolchildren's somatic and mental health - Vondrova, Diana; Kapsdorfer, Daniela; Argalasova, Lubica; Hirosova, Katarina; Samohyl, Martin; Sevcikova, Ludmila (Reviews on environmental health, 2017)
Children develop rapidly and many exogenous determinants of health significantly affect their somatic and mental development. There is a subjective perception of cognitive load associated with the educational process. The aim of the study is to assess individual environmental, behavioral and psychosocial factors influencing physical health and to investigate the amount of mental load in children. We investigated 87 schoolchildren (47 girls and 40 boys) aged 10-12 years, who were attending primary school in Bratislava. To assess values of selected factors we used a questionnaire form and personality characteristics were estimated by standardized psycho-diagnostic and IQ tests [range of classic fear, social-situation anxiety and jitters [skala Klasickeho strachu a Socialno-situacnej (in Slovak)] (KSAT), Eyesenck Personality Questionnaire for children (EPQ), Raven's IQ test]. Self-reported perception of mental load was assessed by questionnaire of subjective feelings and states (SFS). Children's body parameters were assessed using anthropometric measurements [height, weight, chest, abdominal and hip girth, Rohrer's index (RI), body mass index (BMI)] and a body fat measurement method (skinfold thickness). The results confirmed a significant relationship between higher parameters of overweight and obesity and irregular breakfast eating (p<0.05), absence of family dining (p<0.05), exposure to tobacco smoke in the family environment (p<0.01) and mother's level of education (p<0.05). Almost 60% of children reported high mental effort and cognitive load associated with the educational process. We note a close relationship between the higher mental load and the score of neuroticism (p<0.01). The physical and mental health of schoolchildren is significantly affected by exogenous factors. Therefore, in terms of protection and promotion of children's health, it is important to evaluate and monitor environmental risk factors and to form their healthy habits.
Keywords: Child Health; Česká republika; Mental Health; mužské pohlaví; studenti; Czech Republic; dítě; Child; duševní zdraví; ženské pohlaví; Anthropometry; Humans; Students; antropometrie; Health Status; zdravotní stav; Female; zdraví dítěte; lidé; Male